2015
DOI: 10.37190/epe150205
|View full text |Cite
|
Sign up to set email alerts
|

The role of compost properties in sorption of heavy metals

Abstract: The feasibility of various composts to operate as sorbents for heavy metals (Cu and Zn) removal from wastewater has been evaluated. Three commercial composts obtained from municipal solid wastes (MWS), sludge sewage (SS) and poultry manure (PM) were selected as potential sorbents. Kinetic and equilibrium tests were conducted in order to assess the equilibrium conditions to remove metals from aqueous samples. For all composts, the maximum time necessary to reach the equilibrium was 240 min. The Freundlich and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The cation exchange capacity and degree of organic residue decomposition are significantly correlated according many authors (Harada and Inoko 1980;Martinho et al 2015). Therefore this parameter seems to be a good index of compost maturity and indicates a compost's ability to retain nutrients.…”
Section: Resultsmentioning
confidence: 94%
“…The cation exchange capacity and degree of organic residue decomposition are significantly correlated according many authors (Harada and Inoko 1980;Martinho et al 2015). Therefore this parameter seems to be a good index of compost maturity and indicates a compost's ability to retain nutrients.…”
Section: Resultsmentioning
confidence: 94%
“…For the WMC, the qe values were 2.18 mg/g for Cu(II) and 2.22 mg/g for Zn(II), achieved with initial concentrations of 6.0 mg/L. Previous studies on metal retention in various composts yielded qe values of 4.7 mg/g using pine bark compost [30], 12 mg/g using municipal garden waste compost [29], and 11.1 mg/g using municipal solid waste compost [44] for Cu(II). Regarding Zn(II), the qe values were 2.6 mg/g using pine bark compost [30], 12 mg/g using municipal garden waste compost [29], and 6.8 mg/g using municipal solid waste compost [44].…”
Section: Analysis Of Surface Structure Distinctiveness In Retention E...mentioning
confidence: 87%
“…Degradation of organic compounds and synthesis of new connections can significantly alter relations between not only C and N, the content of humic and fulvic acids, but also between total and available forms of trace elements in the composted material. He et al [14] and Martinho et al [15] concluded that the content and speciation of trace elements in composted sewage sludge is a major cause for the negative impact of this material on the environment and health of living organisms.…”
Section: Introductionmentioning
confidence: 99%